APPLICATION EFFECT OF DIFFERENT RATES OF WASTEWATER FROM GELATIN PRODUCTION IN THE CHEMICAL ATTRIBUTES OF THE SOIL - Caroline Silvano; Paulo S. L. Freitas; Roberto Rezende; Liliane S. Mioto; Rivanildo Dallcort (Engenharia Agrícola, 2018)
ABSTRACT The gelatin industry wastewater has nutrients in its composition, allowing its use in agriculture as an alternative to disposal and recycling of this residue. However, high application rates can cause the accumulation of elements such as sodium in the soil, and generate negative impacts on the environment. This study aimed to evaluate the effects of the application of rates up to 600 m3ha-1 of gelatin industry wastewater in soil columns, on soil chemical attributes in five depths. The experiment was conducted in a greenhouse, in PVC tube columns (0.20 m diameter) filled with distroferric Red Nitosol soil, of very clayey texture. The treatments consisted of increasing rates of wastewater equivalent to 0, 150, 300, 450 and 600 m3 ha-1, with a single application, at the soil surface and without incorporation. The application of the gelatin industry wastewater resulted no negative effects on soil chemical properties to a depth of 60 cm. The application of the levels of wastewater increased the concentration of sodium in the soil, but without causing problems with sodicity.